Tingkat Persepsi Peternak Sapi Potong Terhadap Integrasi Sapi-Sawit Di Kecamatan Torgamba Kabupaten Labuhan Batu Selatan Provinsi Sumatera Utara - Sitohang, Afriando; Pramusintho, Bagus; Fatati, * (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the level of beef cattle farmers’ perceptions of the implementation of cattle oil palm integration and to examine the relationship between farmers’ characteristics and perception levels in Torgamba District, South Labuhan Batu Regency, North Sumatra Province. The research employed a survey method with a descriptive quantitative approach. Respondents were selected using random sampling, involving 40 beef cattle farmers. Data were collected through interviews and questionnaires and analyzed using a Likert scale, Chi-Square test, and Spearman Rank correlation test. The results showed that the level of farmers’ perception toward cattle–oil palm integration was categorized as fairly good, with an average value of 69.25%. The assessment indicator recorded the highest score at 72.50%, while the absorption indicator showed the lowest score at 65.50%. The Chi-Square test results indicated that the number of cattle owned had a significant relationship with farmers’ perception levels. Meanwhile, the Spearman Rank correlation analysis revealed that the relationships between farmers’ characteristics (age, education level, farming experience, land area, and number of cattle) and perception were classified as very weak to weak, with correlation coefficients ranging from −0.403 to 0.355. Based on these findings, it can be concluded that farmers’ perceptions of cattle–oil palm integration are fairly good; however, farmers’ characteristics generally have a weak relationship with perception levels. Therefore, improvements in farmers’ perceptions are more strongly influenced by direct experience and the tangible benefits perceived by the farmers.